Collagenase Production by Endotoxin-Activated Macrophages - Wahl, Larry M. (1974)
Peritoneal exudate macrophages, when exposed to bacterial lipopolysaccharide in culture, were found to produce collagenase (EC 3.4.24.3). This enzyme was not detected in extracts of the macrophages or in media from nonstimulated macrophage cultures. Lipidcontaining fractions of the lipopolysaccharide, including a glycolipid from the rough mutant of Salmonella minnesota (R595) and lipid A, were potent stimulators of collagenase production. The lipid-free polysaccharide fraction had no effect. Cycloheximide prevented the production of collagenase by endotoxin-treated macrophages, suggesting that it was newly synthesized.